Public transport travel time perception: Effects of socioeconomic characteristics, trip characteristics and facility usage. (August 2018) - Meng, Meng; Rau, Andreas; Mahardhika, Hita
Abstract: Perceived travel time in public transport trip directly affects passengers' satisfaction and therefore is an essential consideration when planning and operating the public transport system. However, beyond the prevalent analysis on the waiting time perception, there are few articles that have studied the travel time perception along the entire multimodal trip. In this context, this paper presents an empirical investigation of actual and perceived travel time at each stage in a bus-rail transport trip, where first mile, in-vehicle stage, transfer stage and last mile are considered. Data on actual and perceived travel time, socioeconomic characteristics, trip characteristics and facility usage are collected by accompanied survey undertaken from passengers' originations to destinations. The results from a series of paired T -tests show that passenger do perceive travel time to be greater than the actual amount at each stage. Three linear regression models are developed for estimation of perceived walking, waiting and in-vehicle time. Results indicate that socioeconomic characteristics, trip characteristics and facility usage seem to have an impact on passengers' travel time perception, while the travel time spent on the previous stage does not affect the perception much.